Pinpointing regional unconformities in the Surat Basin, Australia, by statistical identification of neutron wireline log anomalies - C. Andrade; P. M. Vasconcelos; I. Rodger; S. Hörning; J. Esterle (Australian Journal of Earth Sciences, 2025)

Opening a can of worms: a test of the co-infection facilitation hypothesis - Maria L. Rodgers; Daniel I. Bolnick (Oecologia, 2024)
Parasitic infections are a global occurrence and impact the health of many species. Coinfections, where two or more species of parasite are present in a host, are a common phenomenon across species. Coinfecting parasites can interact directly or indirectly via their manipulation of (and susceptibility to) the immune system of their shared host. Helminths, such as the cestode Schistocephalus solidus , are well known to suppress immunity of their host (threespine stickleback, Gasterosteus aculeatus ), potentially facilitating other parasite species. Yet, hosts can evolve a more robust immune response (as seen in some stickleback populations), potentially turning facilitation into inhibition. Using wild-caught stickleback from 20 populations with non-zero S. solidus prevalence, we tested an a priori hypothesis that S. solidus infection facilitates infection by other parasites. Consistent with this hypothesis, individuals with S. solidus infections have 18.6% higher richness of other parasites compared to S. solidus -uninfected individuals from the same lakes. This facilitation-like trend is stronger in lakes where S. solidus is particularly successful but is reversed in lakes with sparse and smaller cestodes (indicative of stronger host immunity). These results suggest that a geographic mosaic of host–parasite co-evolution might lead to a mosaic of between-parasite facilitation/inhibition effects.

Sources and concentrations of methane, ethane, and CO2 in deep aquifers of the Surat Basin, Great Artesian Basin - J.K. Pearce; H. Hofmann; K. Baublys; S.D. Golding; I. Rodger; P. Hayes (International Journal of Coal Geology, 2023)

Biological Sound Sources Drive Soundscape Characteristics of Two Australian Marine Parks - Jessica A. McCordic; Annamaria I. DeAngelis; Logan R. Kline; Candace McBride; Giverny G. Rodgers; Timothy J. Rowell; Jeremy Smith; Jenni A. Stanley; Allison Stokoe; Sofie M. Van Parijs (Frontiers in Marine Science, 2021)
Soundscapes represent an intrinsic aspect of a habitat which, particularly in protected areas, should be monitored and managed to mitigate human impacts. Soundscape ecology characterizes acoustic interactions within an environment, integrating biological, anthropogenic, climatological, and geological sound sources. Monitoring soundscapes in marine protected areas is particularly important due to the reliance of many marine species on sound for biological functions, including communication and reproduction. In this study we establish a baseline understanding of underwater soundscapes within two marine National Park Zones (NPZs) along the east coast of Australia: Cod Grounds Marine Park and an NPZ surrounding Pimpernel Rock within Solitary Islands Marine Park. In each of the NPZs, underwater recorders were deployed twice during the austral winter (33–35 days, 2018 and 60–69 days, 2019) and once during the austral summer (35–71 days, 2018–2019). We used the resulting acoustic recordings to determine hourly presence of anthropogenic and biological sounds between 20 Hz and 24 kHz and analyze their contributions to patterns of received sound levels. Sounds from vessels were recorded on most days throughout monitoring but were not found to influence long-term patterns of sound levels over their corresponding frequencies. Biological sources included dolphins, snapping shrimp, fish choruses, humpback whales, and dwarf minke whales. Dolphins, snapping shrimp, and fish choruses were present in all deployments. Median ambient sound levels showed a consistent diel pattern with increased levels resulting from crepuscular fish choruses combined with a higher intensity of snapping shrimp snaps during those times. Singing humpback whales strongly influenced the overall sound levels throughout the winter migration, while dwarf minke whales were consistently detected in the 2019 winter deployment but were only present in 2 h among the earlier deployments. Patterns of acoustic spectra were similar between the two NPZs, and patterns of soundscape measurements were observed to be driven by seasonal differences in biological contributions rather than anthropogenic sound sources, indicating that these NPZs are not yet heavily impacted by anthropogenic noise. These baseline measurements will prove invaluable in long-term monitoring of the biological health of NPZs.

The Society for Environmental Geochemistry and Health (SEGH): building for the future of early career researchers - O. S. Humphrey; D. R. S. Middleton; S. Ahmad; T. Cocerva; S. M. Dowell; R. Garza-Galndo; E. M. Hamilton; N. Kafwamfwa; B. Kaninga; P. Kourgia; I. S. Ligowe; H. A. MacLeod; et al. (Environmental Geochemistry and Health, 2021)

Investigation of co‐infections with pathogens associated with gill disease in Atlantic salmon during an amoebic gill disease outbreak - J K Downes; T Yatabe; M Marcos‐Lopez; H D Rodger; E MacCarthy; I O'Connor; E Collins; N M Ruane (Journal of Fish Diseases, 2018)
Gill diseases are a complex and multifactorial challenge for marine farmed Atlantic salmon. Co‐infections with putative pathogens are common on farms; however, there is a lack of knowledge in relation to the potential effect co‐infections may have on pathology. The objective of this study was to determine the prevalence and potential effects of Neoparamoeba perurans, Desmozoon lepeophtherii , Candidatus Branchiomonas cysticola, Tenacibaculum maritimum and salmon gill poxvirus ( SGPV ) during a longitudinal study on a marine Atlantic salmon farm. Real‐time PCR was used to determine the presence and sequential infection patterns of these pathogens on gill samples collected from stocking until harvest. A number of multilevel models were used to determine the effect of these putative pathogens on gill health (measured as gill histopathology score), while adjusting for the effect of water temperature and time since the last freshwater treatment. Results indicate that between 12 and 16 weeks post‐seawater transfer (wpst), colonization of the gills by all pathogens had commenced and by week 16 of marine production each of the pathogens had been detected. D. lepeophtherii and Candidatus B. cysticola were by far the most prevalent of the potential pathogens detected during this study. Detections of T. maritimum were found to be significantly correlated with temperature showing distinct seasonality. Salmon gill poxvirus was found to be highly sporadic and detected in the first sampling point, suggesting a carryover from the freshwater stage of production. Finally, the model results indicated no clear effect between any of the pathogens. Additionally, the models showed that the only variable which had a consistent effect on the histology score was N. perurans .

Genomes of ubiquitous marine and hypersaline Hydrogenovibrio , Thiomicrorhabdus and Thiomicrospira spp. encode a diversity of mechanisms to sustain chemolithoautotrophy in heterogeneous environments - Kathleen M. Scott; John Williams; Cody M. B. Porter; Sydney Russel; Tara L. Harmer; John H. Paul; Kirsten M. Antonen; Megan K. Bridges; Gary J. Camper; Christie K. Campla; Leila G. Casella; Eva Chase; et al. (Environmental Microbiology, 2018)
Summary Chemolithoautotrophic bacteria from the genera Hydrogenovibrio, Thiomicrorhabdus and Thiomicrospira are common, sometimes dominant, isolates from sulfidic habitats including hydrothermal vents, soda and salt lakes and marine sediments. Their genome sequences confirm their membership in a deeply branching clade of the Gammaproteobacteria . Several adaptations to heterogeneous habitats are apparent. Their genomes include large numbers of genes for sensing and responding to their environment (EAL‐ and GGDEF‐domain proteins and methyl‐accepting chemotaxis proteins) despite their small sizes (2.1–3.1 Mbp). An array of sulfur‐oxidizing complexes are encoded, likely to facilitate these organisms' use of multiple forms of reduced sulfur as electron donors. Hydrogenase genes are present in some taxa, including group 1d and 2b hydrogenases in Hydrogenovibrio marinus and H. thermophilus MA2‐6, acquired via horizontal gene transfer. In addition to high‐affinity cbb 3 cytochrome c oxidase, some also encode cytochrome bd‐ type quinol oxidase or ba 3 ‐ type cytochrome c oxidase, which could facilitate growth under different oxygen tensions, or maintain redox balance. Carboxysome operons are present in most, with genes downstream encoding transporters from four evolutionarily distinct families, which may act with the carboxysomes to form CO 2 concentrating mechanisms. These adaptations to habitat variability likely contribute to the cosmopolitan distribution of these organisms.

In hot water: sustained ocean warming reduces survival of a low-latitude coral reef fish - G. G. Rodgers; J. M. Donelson; M. I. McCormick; P. L. Munday (Marine Biology, 2018)

Oxidative stress is associated with late‐stage amoebic gill disease in farmed Atlantic salmon ( Salmo salar L.) - M Marcos‐López; C Ruiz Espinosa; H D Rodger; I O'Connor; E MacCarthy; M A Esteban (Journal of Fish Diseases, 2018)

Piscine myocarditis virus detected in corkwing wrasse ( Symphodus melops ) and ballan wrasse ( Labrus bergylta ) - F Scholz; N M Ruane; T Morrissey; M Marcos‐López; S Mitchell; I O'Connor; L Mirimin; E MacCarthy; H D Rodger (Journal of Fish Diseases, 2018)

First record of Tetramicra brevifilum in lumpfish ( Cyclopterus lumpus, L.) - F Scholz; E Fringuelli; M Bolton‐Warberg; M Marcos‐López; S Mitchell; P Prodhol; D Moffet; P Savage; S Murphy O'Sullivan; I O′Connor; E McCarthy; H D Rodger (Journal of Fish Diseases, 2017)
A microsporidian species with 98.3–98.4% nucleotide identity to Tetramicra brevifilum ( Journal of Fish Diseases , 3 , 1980, 495) was diagnosed in lumpfish ( Cyclopterus lumpus , L.) broodstock held at a breeding and rearing facility in western Ireland. The fish were wild‐caught from the west coast of Ireland, and the first case was diagnosed one year after capture. Clinical signs included severe bloating, lethargy, exophthalmos, anorexia, white patches on the cornea and externally visible parasitic cysts on skin and fins. Necropsy revealed severe ascites, white nodules and vacuoles in all the internal organs and partial liquefaction of the skeletal muscle. On histological examination, microsporidian xenomas were observed in all internal organs, the skin, skeletal muscle, gills and the eyes. The microsporidian species was identified by molecular analysis and transmission electron microscopy. This is the first record of T. brevifilum infecting lumpfish, and the disease is considered to be of potential significance to the rising aquaculture industry of this species.

Natural attenuation of coal combustion waste in river sediments - James T. Markwiese; William J. Rogers; Neil E. Carriker; David I. Thal; Rock J. Vitale; Jacob G. Gruzalski; Erin E. Rodgers; Carol M. Babyak; Randall T. Ryti (Environmental Monitoring and Assessment, 2014)

Geographical distribution of salmonid alphavirus subtypes in marine farmed Atlantic salmon, Salmo salar L., in Scotland and Ireland - D A Graham; E Fringuelli; H M Rowley; D Cockerill; D I Cox; T Turnbull; H Rodger; D Morris; M F Mc Loughlin (Journal of Fish Diseases, 2012)
Sequence data from salmonid alphavirus (SAV) strains obtained from farmed marine Atlantic salmon, Salmo salar L. , over a 20‐year period between 1991 and 2011 was reviewed to examine the geographical distribution of the genetically defined SAV subtypes in twelve regions across Ireland and Scotland. Of 160 different Atlantic salmon SAV strains examined, 62 belonged to subtype 1, 28 to subtype 2, 34 to subtype 4, 35 to subtype 5 and 1 to subtype 6. SAV subtypes 1, 4 and 6 were found in Ireland, while subtypes 1, 2, 4 and 5 were found in Scotland. In the majority of regions, there was a clear clustering of subtypes, with SAV subtype 1 being the dominant subtype in Ireland overall, as well as in Argyll and Bute in Scotland. SAV subtype 2 predominated in the Shetland and Orkney Islands. The emergence in Atlantic salmon of subtype 2 strains typically associated with sleeping disease in rainbow trout in Argyll and Bute, strongly suggesting transmission of infection between these species, was noted for the first time. SAV subtype 4 was the most common subtype found in the southern Western Isles, while SAV subtype 5 predominated in the northern Western Isles and north‐west mainland Scotland. No single strain was dominant on sites in the western Highlands, with a number of sites in this region in particular having more than one subtype detected in different submissions. The significance of these results in relation to aspects of the epidemiology of infection, including transmission, biosecurity and wildlife reservoirs are discussed and knowledge gaps identified.

Ocean acidification and calcifying reef organisms: a mesocosm investigation - P. L. Jokiel; K. S. Rodgers; I. B. Kuffner; A. J. Andersson; E. F. Cox; F. T. Mackenzie (Coral Reefs, 2008)

Mechanisms for Flow-Enhanced Cell Adhesion - Cheng Zhu; Tadayuki Yago; Jizhong Lou; Veronika I. Zarnitsyna; Rodger P. McEver (Annals of Biomedical Engineering, 2008)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

Abnormal gonadal morphology in intersex, Echinogammarus marinus (Amphipoda): a possible cause of reduced fecundity? - A. T. Ford; T. P. Rodgers-Gray; I. M. Davies; A. M. Dunn; P. A. Read; C. D. Robinson; J. E. Smith; T. F. Fernandes (Marine Biology, 2005)

Abnormal gonadal morphology in intersex, Echinogammarus marinus (Amphipoda): a possible cause of reduced fecundity? - A. T. Ford; T. P. Rodgers-Gray; I. M. Davies; A. M. Dunn; P. A. Read; C. D. Robinson; J. E. Smith; T. F. Fernandes (Marine Biology, 2005)

Ecogeochemistry of the subsurface food web at pH 0–2.5 in Iron Mountain, California, U.S.A. - Eleanora I. Robbins; Teresa M. Rodgers; Charles N. Alpers; D. Kirk Nordstrom (Hydrobiologia, 2000)

Ultrastructure and composition of Call-Exner bodies in bovine follicles - I. L. van Wezel; H.F. Irving-Rodgers; Y. Sado; Y. Ninomiya; R. J. Rodgers (Cell and Tissue Research, 1999)

Characterization of CHO-K1 cells stably expressing PDE-IV enzymes - D. J. Pon; M. Plant; J. Tkach; L. Boulet; E. Muise; R. A. Allen; I. W. Rodger (Cell Biochemistry and Biophysics, 1998)